2012
DOI: 10.1111/j.1745-4514.2011.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

ANTIOXIDANT POTENCY, pH AND HEAT STABILITY OF SELECTED PLANT EXTRACTS

Abstract: The potential of methanolic extracts of six green leafy vegetables, viz. Punica granatum, Ipomoea batatas L., Beta vulgaris, Daucus carota, Amaranthus paniculatus and Peucedanum graveolens, as a natural antioxidant was assessed. Two experimental models, namely 1,1‐diphenyl‐2‐picrylhydrazyl radical‐scavenging activity and iron (III) reducing capacity, were used to evaluate the antioxidant activity (AOA) of green leafy vegetables. The stability of extracts to pH (4, 7 and 9) and temperature (100C) was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Phenolic compounds are considered as effective hydrogen donor that makes them good antioxidant [ 54 ]. The results of the present study corroborate the results of previous studies where it has been reported that plant phenolic compounds govern antioxidant activity of plant extracts [ 28 , 55 57 ]. Therefore, aqueous extract of Moringa oleifera flower pods can be considered as a potent source of natural antioxidants.…”
Section: Resultssupporting
confidence: 92%
“…Phenolic compounds are considered as effective hydrogen donor that makes them good antioxidant [ 54 ]. The results of the present study corroborate the results of previous studies where it has been reported that plant phenolic compounds govern antioxidant activity of plant extracts [ 28 , 55 57 ]. Therefore, aqueous extract of Moringa oleifera flower pods can be considered as a potent source of natural antioxidants.…”
Section: Resultssupporting
confidence: 92%
“…A high content of total phenolics in methanol (86.16 ± 4.51 mg catechin/g) and acetone (78.8 ± 5.3 mg catechin/g) extracts was also reported for radish leaves by [16]. Results lower than those found in this study were reported by [14] , for the methanol extract of carrot (9.3 mg GAE/g), beet (6.1 mg GAE/g), and sweet potato (17.3 mg GAE/g) leaves. The difference between the reported values was possibly due to the use of only one type of solvent, which may have compromised the extraction efficiency of phenolic compounds.…”
Section: Identification and Quantification Of Twelve Phenolic Compounsupporting
confidence: 50%
“…Several studies reported the potential of tuberous root leaves as nutraceutical food. The leaves of carrot (Daucus carota L.) are natural sources of omega 3 and 6 [10] and are used in salads, soups, and in the preparation of food products; [10][11][12] beet (Beta vulgaris L.) leaves are used in food formulations to increase their nutritional value [13] ; the leaves of sweet potato (Ipomea batatas L.) have a high content of soluble fiber, polyphenols, and minerals, especially iron and vitamin E; [14] yam (Colocasia esculenta L.) leaves are consumed in sauces, purées, stews, and soups and are used in the treatment of scarring; [15] and radish (Raphanus sativus L.) leaves present a broad spectrum of antibacterial activity against foodborne pathogens. [16] Although several studies elucidated the antioxidant potential of most of these leaves, few analyze the content of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant effect of several genus of Peucedanum has been confirmed [14] . The methanolic extract of Peucedanum graveolens has a high thermal and pH stability, and its antioxidant effect increases at high temperatures and pH levels [44] . In this study, two antioxidant tests, DPPH and iron chelating, were used [14] .…”
Section: Discussionmentioning
confidence: 99%